On the identification of Frisch labor supplies - Olivier Donni (Institute for the Study of Labor (IZA), 2006)
This paper examines how Frisch labor supplies, and other structural components of the intertemporal model of labor supply, can be recovered from estimates obtained with the approach developed by Heckman and MaCurdy.
Keywords: J22; 330; labor supply; Frisch; life cycle; identification; Arbeitsangebot; Lebenszyklus; Theorie